Protein tyrosine phosphatase-1B modulates pancreatic β-cell mass. - Rebeca Fernandez-Ruiz; Elaine Vieira; Pablo M Garcia-Roves; Ramon Gomis (PLoS ONE)
Protein tyrosine phosphatase 1B (PTP1B) is a negative regulator of the insulin signalling pathway. It has been demonstrated that PTP1B deletion protects against the development of obesity and Type 2 Diabetes, mainly through its action on peripheral tissues. However, little attention has been paid to the role of PTP1B in β-cells. Therefore, our aim was to study the role of PTP1B in pancreatic β-cells. Silencing of PTP1B expression in a pancreatic β-cell line (MIN6 cells) reveals the significance of this endoplasmic reticulum bound phosphatase in the regulation of cell proliferation and apoptosis. Furthermore, the ablation of PTP1B is able to regulate key proteins involved in the proliferation and/or apoptosis pathways, such as STAT3, AKT, ERK1/2 and p53 in isolated islets from PTP1B knockout (PTP1B (-)/(-)) mice. Morphometric analysis of pancreatic islets from PTP1B (-)/(-) mice showed a higher β-cell area, concomitantly with higher β-cell proliferation and a lower β-cell apoptosis when compared to islets from their respective wild type (WT) littermates. At a functional level, isolated islets from 8 weeks old PTP1B (-)/(-) mice exhibit enhanced glucose-stimulated insulin secretion. Moreover, PTP1B (-)/(-) mice were able to partially reverse streptozotocin-induced β-cell loss. Together, our data highlight for the first time the involvement of PTP1B in β-cell physiology, reinforcing the potential of this phosphatase as a therapeutical target for the treatment of β-cell failure, a central aspect in the pathogenesis of Type 2 Diabetes.